2021
DOI: 10.1111/1346-8138.15719
|View full text |Cite
|
Sign up to set email alerts
|

Dietary habits in Japanese patients with palmoplantar pustulosis

Abstract: Palmoplantar pustulosis (PPP) is a chronic dermatitis characterized by sterile intra‐epidermal pustules associated with erythema and scales on the palms and soles. Tumor necrosis factor (TNF)‐α/interleukin (IL)‐23/IL‐17 inflammatory pathway may be involved in the pathogenesis of PPP, and the skin lesions manifest the enhanced expression of IL‐8 in keratinocytes and increased levels of antimicrobial peptide cathelicidin, leucine leucine‐37 in vesicles/pustules. Some PPP patients are associated with arthro‐ostei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 56 publications
2
5
0
Order By: Relevance
“…16 We also aimed to identify whether there is an association between obesity and disease severity, as few studies have examined this association. 3,9,17 Consistent with two previous studies, 3,9 we found no association between higher PPPASI and either mean BMI or frequency of overweight/obesity. However, Serizawa et al 17 recently reported that BMI was a predictor for PPPASI, therefore this association warrants further investigation.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…16 We also aimed to identify whether there is an association between obesity and disease severity, as few studies have examined this association. 3,9,17 Consistent with two previous studies, 3,9 we found no association between higher PPPASI and either mean BMI or frequency of overweight/obesity. However, Serizawa et al 17 recently reported that BMI was a predictor for PPPASI, therefore this association warrants further investigation.…”
Section: Discussionsupporting
confidence: 91%
“…This can be explained by the fact that both BMI and prevalence of obesity is considerably higher in Turkish women (30%) than in men (17%) in the general Turkish population 16 . We also aimed to identify whether there is an association between obesity and disease severity, as few studies have examined this association 3,9,17 . Consistent with two previous studies, 3,9 we found no association between higher PPPASI and either mean BMI or frequency of overweight/obesity.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Obesity/high body mass index (BMI) is another risk factor for PPP (OR 1.21, p=0.0009). 16 , 17 , 24 However, it is unclear whether obese people have a higher risk for the development of PPP than PV, with higher risk reported in a cross-sectional study but not in a case-control study. 7 , 24 Disease severity (PPPASI) is predicted by BMI (p=0.0444).…”
Section: Resultsmentioning
confidence: 99%
“… 7 , 24 Disease severity (PPPASI) is predicted by BMI (p=0.0444). 17 Other alimentary risk factors are listed in Table 1 . 17 Insulin resistance was not a risk factor.…”
Section: Resultsmentioning
confidence: 99%